1984
DOI: 10.1111/j.1151-2916.1984.tb18848.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Glasses with Molar Composition 20Na2O · 10RO ·x Al2O3· (70‐x)SiO2

Abstract: as a Microwave Dielectric Resonator," J . Am. Ceram. Soc., 58 19-10] 418-20 (1975). 'S. Kawashima, M. Nishida, I. Ueda, and H. Ouchi, "Dielectnc Properties of Ba(Zn,,,Nb2,,)0,-Ba(Zn ,,3Ta,,)0, Ceramics at Microwave Frequency": pp. 293-96 in ,)O, Ceramics with Temperature-Stable High Dielectric Constant and Low Microwave Loss," Jpn. J. Appl. Phys., 21 [lo] L624-26 (1982). Sodium depth profiles were determined in water-leached glass samples with molar composition 20Na20 * lORO *xA1203* (70x)Si02 (RO = CaO, MgO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…12 For glasses with low concentrations of Al 2 O 3 (<3.5 mol%), they suggest 7-day PCT measurements are dominated by Stage I behavior as ion-exchange processes are faster leading to increased pH, higher Si solubility, and delayed transition to stage II. [44][45][46] For intermediate concentrations (3.5 to 19 mol%), relatively low NL(α) values indicate that the glass dissolution rate slowed (which may be an indication of a transition to Stage II behavior). High NL(α) values observed with glasses with high Al 2 O 3 concentrations (>19 mol%) may be evidence that they are already undergoing Stage III behavior.…”
Section: Decomposition Of Raman Spect On Glass Composition From Td Modelmentioning
confidence: 99%
“…12 For glasses with low concentrations of Al 2 O 3 (<3.5 mol%), they suggest 7-day PCT measurements are dominated by Stage I behavior as ion-exchange processes are faster leading to increased pH, higher Si solubility, and delayed transition to stage II. [44][45][46] For intermediate concentrations (3.5 to 19 mol%), relatively low NL(α) values indicate that the glass dissolution rate slowed (which may be an indication of a transition to Stage II behavior). High NL(α) values observed with glasses with high Al 2 O 3 concentrations (>19 mol%) may be evidence that they are already undergoing Stage III behavior.…”
Section: Decomposition Of Raman Spect On Glass Composition From Td Modelmentioning
confidence: 99%
“…The differences in fluorescence enhancement due to the PET-effect for the bulk sample (5-fold as shown in Figure 3) compared to the MOF experiments (21.4–36.4% as in Figure 4) may be due to leaching of Na + or K + ions from the lead-silicate glass, resulting in a raised background fluorescence signal as the FI responds to the increased alkali cation concentration and consequently limiting the fluorescence enhancement when measuring spiked sodium solutions. Leaching under relatively benign conditions has been reported [36]. Future mitigation strategies include the use of coatings on the MOF surfaces or the use of alternative glass compositions.…”
Section: Resultsmentioning
confidence: 99%
“…In the second mechanism, alumina increased the glass network connectivity and resulted in a decrease of water diffusivity. 83 By using secondary ion mass spectrometry (SIMS), Smets and Tholen found that alumina also stabilized 4-fold coordinated Mg and Zn, hence further improving the glass durability. 83 Corrosion of SLS glass with alumina was studied by Wassick et al 85 using nuclear reaction and Rutherford backscattering to determine the hydrogen and sodium profiles, respectively, of the corroded glass surfaces.…”
Section: Composition Effectsmentioning
confidence: 99%
“…83 By using secondary ion mass spectrometry (SIMS), Smets and Tholen found that alumina also stabilized 4-fold coordinated Mg and Zn, hence further improving the glass durability. 83 Corrosion of SLS glass with alumina was studied by Wassick et al 85 using nuclear reaction and Rutherford backscattering to determine the hydrogen and sodium profiles, respectively, of the corroded glass surfaces. It was found that the addition of a small amount of Al 2 O 3 could improve the chemical durability, which was explained by the suppression of the formation of a surface alteration layer that has high ion mobility.…”
Section: Composition Effectsmentioning
confidence: 99%
See 1 more Smart Citation